2021
DOI: 10.1186/s12877-021-02441-1
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-informed care in geriatric inpatient units to improve staff skills and reduce patient distress: a co-designed study protocol

Abstract: Background Geriatric hospital wards are highly medicalised environments with limited opportunities for choice and control, and can be distressing for older survivors of psychological trauma. While trauma-informed models of care (TIC) are effectively applied across mental health and other settings, the utility of these models in aged care settings has not been assessed. The objective of this study was to examine whether TIC can reduce responsive behaviour, chemical restraint, and improve staff s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…PCC is widely regarded as a best‐practice approach to caring for older people living in RAC 54,56–58 and is focused on interpreting and regulating unmet needs, relational aspects of care and the impact of environments on behaviours, 59 which aligns with the principles of TIC 6,17,31 . Additionally, the documented outcomes of PCC align with those of TIC, including improved resident wellbeing and quality of life, reduced psychological distress, improvements in staff job satisfaction and wellbeing and reduced burnout and work‐related stress 58,60–62 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PCC is widely regarded as a best‐practice approach to caring for older people living in RAC 54,56–58 and is focused on interpreting and regulating unmet needs, relational aspects of care and the impact of environments on behaviours, 59 which aligns with the principles of TIC 6,17,31 . Additionally, the documented outcomes of PCC align with those of TIC, including improved resident wellbeing and quality of life, reduced psychological distress, improvements in staff job satisfaction and wellbeing and reduced burnout and work‐related stress 58,60–62 …”
Section: Discussionmentioning
confidence: 99%
“…6,17,31 Additionally, the documented outcomes of PCC align with those of TIC, including improved resident wellbeing and quality of life, reduced psychological distress, improvements in staff job satisfaction and wellbeing and reduced burnout and work-related stress. 58,[60][61][62] Whilst TIC is not specifically PCC as it is more broadly focused on the impacts of trauma on clients, staff and the organisation, there are highlighted overlaps from this review. This review highlighted examples where PCC approaches, which may be effective with some older people, are re-traumatising and problematic when that older person also has a trauma history 44 and is inconsistent with TIC.…”
Section: Tic Reflects Pcc Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were identified by searching two electronic databases: PsycINFO and PubMed. In protocol studies (e.g., Cations et al, 2021) or studies describing multiple projects (e.g., Longhi et al, 2021), a manual search was performed in Google to see if any additional or independent articles on each project had been published with results.…”
Section: Methodsmentioning
confidence: 99%
“…The third ward is a 12-bed specialized unit for people with dementia and associated behavior change, with single patient rooms and medical, nursing and allied health professional staffing. The staff were engaged in a training and mentoring program to improve the delivery of trauma-informed care within the service ( 17 ). However, none of the wards included staffing from psychiatry, psychology, or mental health nursing although consultation could be sought from external mental health services where needed.…”
Section: Methodsmentioning
confidence: 99%